2019
DOI: 10.1136/bjophthalmol-2019-315199
|View full text |Cite
|
Sign up to set email alerts
|

Real-world management of treatment-naïve diabetic macular oedema in Japan: two-year visual outcomes with and without anti-VEGF therapy in the STREAT-DME study

Abstract: Background/AimsTo investigate real-world outcomes for best-corrected visual acuity (BCVA) after 2-year clinical intervention for treatment-naïve, centr-involving diabetic macular oedema (DME).MethodsRetrospective analysis of longitudinal medical records obtained from 27 institutions specialising in retinal diseases in Japan. A total of 2049 eyes with treatment-naïve DME commencing intervention between 2010 and 2015 who were followed for 2 years were eligible. Interventions for DME included anti-vascular endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…In this study, all data were obtained from STREAT-DMO database in Japan, previously described. 17 In brief, this retrospective observational study included all eligible patients who received a diagnosis of treatment-naïve centre involving DMO, started initial treatment between January 2010 and December 2015, and were followed for 2 years (22–26 months). Baseline clinical data obtained from the medical record of each patient included the age, gender, duration of diabetes, glycohaemoglobin and estimated glomerular filtration rate calculated from the creatinine level at initiation of treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, all data were obtained from STREAT-DMO database in Japan, previously described. 17 In brief, this retrospective observational study included all eligible patients who received a diagnosis of treatment-naïve centre involving DMO, started initial treatment between January 2010 and December 2015, and were followed for 2 years (22–26 months). Baseline clinical data obtained from the medical record of each patient included the age, gender, duration of diabetes, glycohaemoglobin and estimated glomerular filtration rate calculated from the creatinine level at initiation of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The database, Survey of Treatment for DMO (STREAT-DMO), consisted of more than 2000 medical records from a demographically and geographically diverse patient sample in Japan, including all eligible patients who had diagnosed centre involving DMO without any previous interventions, and started initial treatment for centre involving DMO between January 2010 and December 2015, and had been followed for 2 years. 17 Within this period, anti-VEGF agents of ranibizumab (February 2014) and aflibercept (November 2014) were approved to DMO in Japan. Thus, treatment patterns for DMO and its visual prognosis must be changed by year, but there were no reports about fluctuation of visual prognosis and intervention required for centre-involving DME by year to year.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread use of anti-VEGF agents, there is wide variability in patient outcomes. This variability was initially apparent in clinical trials, where a significant proportion of patients failed to achieve a functional or anatomical response [ 78 ] but is even more striking in the real-world clinical setting [ 79 ]. While some of these variations in treatment response can be explained by clinical and environmental factors, it has been postulated that inherited genetic variation may also play a role.…”
Section: Genetic Predictors Of Treatment Responsementioning
confidence: 99%
“…This study used the same criteria as the VISTA and VIVID studies and excluded poorly controlled diabetes mellitus patients in order to compare the results more accurately. As a result, the mean HbA1c of the enrolled patients was 7.2 ± 1.0%, which was relatively low, while the mean HbA1c was 7.7 ± 1.8% in a study of real-world DME treatment in Japan reported by Shimura et al 34 . This discrepancy could have affected the results.…”
Section: Discussionmentioning
confidence: 81%
“…Pivotal randomized clinical trials (RCTs) that used bevacizumab 4 , ranibizumab 5 , and aflibercept 6 also reported that anti-VEGF therapy carries better efficacy than focal/grid laser; therefore, anti-VEGF therapy is the first line treatment for DME now. However, while the excellent effects of anti-VEGF therapy have been widely accepted, we also have found that the proposed regimens by the aforementioned RCTs in patients with DME 7 or age-related macular degeneration 8 is not always possible in real-world settings 9 . A majority of the RCTs employed fixed-dosing regimens, such as monthly 5 , 10 or bimonthly 11 , 12 injections, which requires frequent hospital visits.…”
Section: Introductionmentioning
confidence: 98%